CONFERINȚA FINALĂ A PROGRAMULUI CHIȘINĂUL CITEȘTE – ROMANUL KINDERLAND DE LILIANA KOROBCA - MUNTEAN, director, Biblioteca Centrală a BM „B.P. Hasdeu”, Liuba (BIBLIOPOLIS, 2020)
In a country where the crisis in the economy and chaos prevails in all spheres of society, more and more parents are forced to leave their children with grandparents and go abroad in search of a better future. The fate of these children is described in detail in the Kinderland novel by Liliana Korobca.